Reclamation performance assessment at PT. Trubaindo Coal Mining in Melak field, West Kutai, East Kalimantan Province, Indonesia - Gastramat, Maria Frumensia; Fanani, Yazid; Galih Cahyono, Yudho Dwi (Journal of Earth and Marine Technology (JEMT), 2024)
Trubaindo Coal Mining Ltd. was established on March 13, 1990, as a subsidiary of Banpu Company. Based in Thailand, Banpu operates within the coal mining industry. Mining activities can have adverse effects, including habitat disruption for flora and fauna, morphological alterations, and reduced soil productivity. To mitigate these impacts, reclamation activities are essential. In compliance with PERMENHUT Number P.60/Menhut-II/2009 and the Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM/Year 2018, assessing the success of reclamation efforts is a critical step. This study aims to assess and evaluate reclamation activities conducted during the production operation phase at Trubaindo Coal Mining Ltd., focusing on land areas within Pit 3000 BK-04 NB and Pit 4500/P6200 BK03-04 SB1. The research employed a quantitative descriptive method, which included observations on land preparation, revegetation efforts, and final land stabilization. The findings revealed reclamation success rates of 87.3 and 83.1, indicating that the reclamation efforts were generally acceptable but required further improvements. Recommendations include soil pH correction, enhancement of drainage channels, and effective management of weeds, pests, and plant diseases.